Comparison of Clotrimazole and Boric Acid in Treatment of Complicated Vulvovaginal Candidiasis - M Zeinalzadeh, (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Vulvovaginal candidiasis is a frequent disease among women and the complicated one is more resistant to treatment. It has a high recurrence rate. This study was carried out to compare two treatment regimens: intravaginal clotimazole and boric acid for treatment and recurrence rate of complicated vulvovaginitis.METHODS: This clinical trial study was performed on 60 women with clinical and mycological evidence of complicated vaginal candidiasis that referred to Yahyanejad hospital, Babol, Iran. They were randomized to receive daily intravaginal boric acid for 14 days (30 women) or daily intravaginal clotrimazole for 14 days (30 women). They were assessed 1 month and 3 months after treatment and compared together. FINDINGS: Twenty three patients (76.7%) was cured clinically for inflammation and 25 patients (83.3%) for discharge and 18 patients (60%) microscopically in clotrimazole group and 24 patients (80%) was cured clinically for inflammation and discharge and 19 patients (63.3%) microscopically in boric acid group. The rate of microscopically recurrence was 7 patients (38.9%) in clotrimazole group and 5 patients (26.3%) in boric acid group. These differences were not statistically significant.CONCLUSION: The study suggests that boric acid or clotrimazole is effective in treatment and recurrence of complicated vaginal candidasis. It is more cost effective to use boric acid.